Construction of The Bakauheni-Terbanggi Besar Toll Road to Improve The Community's Economy - Frenky Andriawan Lubis; Ana Silviana (Eduvest - Journal of Universal Studies, 2023)
Infrastructure development in Lampung, especially toll roads, is urgently needed to support mobility, increase the distribution of goods and services, especially in areas with high levels of devel-opment and it can reduce congestion on a number of Trans-Sumatra Roads in Lampung, there some points or areas are the main routes, which is able to support the economy constrained by traffic jams and inadequate roads. This study aims to examine whether the construction of the toll road has had the expected im-pact and achieved the above goals. A number of sectors are used as the main study in this research, namely Population, Employ-ment and Unemployment; Industrial and Commercial; Retail; Housing area; and Business Operational Efficiency. This study us-es empirical studies, which use field data as the main source, such as the results of interviews and observations. The results of the study show that the positive impact of infrastructure development in the short term has been felt by the community, especially in terms of business and retail operational efficiency. However, vari-ous studies have stated that the biggest impact on infrastructure development is in the future, especially with massive population growth which will certainly increase the capacity of the economic ecosystem, even forming a new economic ecosystem